Total Quality Management: Pendekatan Sejarah dan Konsep Mutu Pendidikan - Yusri A Boko (Foramadiahi: Jurnal Kajian Pendidikan dan Keislaman, 2021)
The development of technology demands an increase in the quality of education invarious aspects, one of which is quality. This article aims to describe; 1) The history of TQM,and 2) The concept of school quality with a library approach. Total Quality Management(TQM) or the history of integrated quality is late in the West, although the ideas wereoriginally developed in the 1930s and 1940s by W. Edwards Deming. Deming beganformulating his ideas in the 1930s while conducting research on methods of eliminatingvariability and waste from industrial processes used by the Japanese government. Demingfirst visited Japan in the late 1940s to conduct a post-war census of Japan. Impressed by hisperformance, the Japanes Union of Engineers and Scientists invited Deming to return in 1950to teach the application of statistical process control to industry players in Japan. Japanpressed attention in reconstructing their war-damaged industry. This is where Japan initiallycampaigned for the quality movement. The concept of quality, quality as an absolute conceptin the category of goods, then quality goods are goods that are very valuable to someone, thegoods are physically very good, beautiful, elegant, luxurious, antique, without defects, strongand other sizes that usually associated with goodness (goodness), beauty (beauty), truth.